Finding Relief in Action: The Intersection of Youth-Led Community Organizing and Mental Health in Brooklyn, New York City. Issue 4 (May 2020) - Ortega-Williams, Anna; Wernick, Laura J.; DeBower, Jenny; Brathwaite, Brittany
Youth of Color, especially those in households with low income, experience multiple stressors and trauma that affect their well-being. Few studies examine the impact of youth engagement in leadership and organizing to address systemic inequity on their mental health and well-being. In a community-based participatory action research design, three organizations which train youth of Color in organizing in Brooklyn, New York, held four focus groups ( n = 43, ages 14-24 years) to examine the impact of organizing on youth mental health and well-being. Key emergent themes of youth organizing include (a) storytelling as therapeutic; (b) group leadership as strengthening personal and collective power, hopefulness, and a sense of protection; and (c) the strain of navigating their hopes and current reality. This study has important implications for actions programs can take who seek to engage youth of Color in organizing in communities and institutions impacted by historical trauma and current day systemic inequity.